Bibliometric Analysis Of English Educational Research Indexed Scopus Q1 With Vosviewer In 2023 - Aqilah, Jasmine Syifa; Siahaan, Leroy Holman; Solo, Lenny (Innovative: Journal Of Social Science Research, 2024)
This study conducts a bibliometric analysis of research on English education indexed in Scopus Q1 journals using VOSviewer in 2023. The analysis aims to identify trends in research methodology and topics in English language teaching, focusing on key skills such as listening, speaking, reading, and writing. The study takes a quantitative method, collecting data from Scopus and analyzing co-occurrence connections between terms. The findings suggest two key clusters of topics: one concentrated on "English language skills" and their relationship to current teaching techniques like as e-learning, particularly during the COVID-19 epidemic, and the other on language requirements in military education. The findings help to understand the history of English language education research and lay the groundwork for future studies in the discipline